The uneven path of British Liberalism : From Jo Grimond to Brexit, second edition - Jones, Tudor, 1946- (Book collections on Project MUSE., 2019)
"[At the end of the Second World War, the Liberal Party was on the point of collapse. Once a major force in British politics, it had been relegated to the sidelines by the rise of Labour and a resurgent Conservative Party. But the distinctive principles of British Liberalism were to prove remarkably resilient, and subsequent decades would witness the Party's gradual revival and a dramatic struggle for its soul. This book charts the evolution of Liberal politics, starting with Jo Grimond's leadership during the Suez Crisis of 1956 and following the uneven path of the Liberal revival to the 2015 general election and the 2016 EU referendum - two setbacks that threw British Liberalism into crisis once more. Drawing on interviews with leading politicians and thinkers, including Vince Cable, Paddy Ashdown, David Owen and Shirley Williams, the book examines Liberal ideas against the background of key historical events and controversies, including the period of coalition government with the Conservatives. With the Liberal Democrats emerging once again from a period of electoral disaster, this book provides an unparalleled account of the ideas and values that have made them a perennial force in British politics." -- Back cover.